Unveiling Regional Disparities in Indonesia: Clustering Provinces by Development Indicators - Yusman, Akbarrullah; Berliana, Sarni Maniar (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Indonesia’s pursuit of sustainable development—integrating economic, social, and environmental dimensions—remains challenged by persistent regional disparities. In 2022, only four of seven national priority indicators were achieved, while 21 provinces failed to meet more than three targets. To capture these disparities more precisely, this study applies hierarchical and non-hierarchical clustering to classify 34 provinces based on seven development indicators. The comparative approach enhances robustness: hierarchical clustering reveals inter-provincial linkages, while non-hierarchical clustering improves internal consistency. Validation tests identify Ward’s method as optimal, yielding four distinct clusters. Cluster 1 includes four eastern provinces with multidimensional inequality—high stunting (31.43%), early marriage (10.37%), and low literacy (36.44%). Cluster 2 comprises 20 provinces with structural stagnation, marked by persistent stunting (24.80%) and reliance on primary sectors. Cluster 3 consists of seven industrial provinces with strong economic performance (manufacturing 33.59% of GDP) and improving social indicators. Cluster 4 includes three service-based provinces excelling in social outcomes—lowest stunting (13.07%) and highest literacy (78.46%)—but facing environmental challenges. These findings highlight the urgency of region-specific, evidence-based policy interventions to promote equitable and sustainable development.